The Waite Group's UNIX system V primer : - Waite, Mitchell (Sams, 1992)
A hands-on introduction to using UNIX! This text provides an updated, detailed overview of the UNIX operating system. Provides a step-by-step introduction to UNIX. Offers many examples and exercises. Reinforces learning with question-and-answer chapter reviews. Covers Through System V.